Use of a Newly Developed Delivery Device for Percutaneous Introduction of Multiple Lead Configurations for Spinal Cord Stimulation. Issue 5 (25th February 2014) - Raso, Louis J.; Deer, Timothy R.; Schocket, Sandford M.; Chapman, Jack A.; Duarte, Luis E.; Justiz, Rafael; Amirdelfan, Kasra; Paicius, Richard M.; Navalgund, Yeshvant A.; Girardi, George E.; Coleman, Neal E.; Verdolin, Michael; et al.
<x xml:space="preserve">Abstract</x> Objective The Epiducer lead delivery system is a novel lead delivery device that can be used to percutaneously implant S‐Series paddle leads (St. Jude Medical, Plano, TX, USA) as well as multiple percutaneous leads obviating the need for laminectomy and/or multiple needle sticks, respectively. This study evaluates the safety and usage of the Epiducer lead delivery system. Methods An Institutional Review Board‐approved observational data collection study was conducted to evaluate usage patterns of the Epiducer system. In addition to the number and frequency of different lead configurations, the following procedural aspects of the surgery were recorded during the evaluation: angle of entry, distance from entry to final lead placement, and physician feedback. Descriptive statistics on adverse events, procedural aspects, and patient outcomes were compiled. Results Data were collected from 163 patients across 25 investigational sites. Physicians successfully implanted patients using the Epiducer during 89% of the procedures. Seven possible lead configurations were implanted. There were 96% and 92% of physicians "satisfied" or "very satisfied" with accessing the epidural space and placing multiple leads with the Epiducer delivery system, respectfully. Eighty‐nine percent of physicians were "satisfied" or "very satisfied" with implanting an S‐Series paddle lead using the Epiducer delivery system. Ninety‐five percent of physicians were "satisfied" or "very satisfied" with the Epiducer delivery system overall. Ten patients (6%) experienced adverse events. Conclusion Results suggest that the Epiducer delivery system allows for the safe and successful percutaneous implantation of paddle leads and/or multiple lead configurations. Furthermore, physicians are satisfied with the Epiducer delivery system.